HUBUNGAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA DAN LOYALITAS MAHASISWA DITINJAU DARI MODEL PEMBELAJARAN DI AKADEMI FARMASI SURABAYA - Abd. Syakur (Universitas Tribhuwana Tunggadewi, 2018)
Abstract: Higher Education as an institution of education service providers are required to provide services that can create maximum satisfaction to the community of its services users, which in turn will be able to encourage the progress of the Higher Education. The research was conducted at Akademi Farmasi Surabaya. The research used responder students, staff and lecturers, chosen randomly. Or also using 30 questions consisting of data analysis process used by the researcher is using multiple linear regression test analysis obtained from the relationship between service quality and student satisfaction as service user to student loyalty. The result showed that for service quality variables obtained the value of t arithmetic of 2.454 with a value of p-value of 0.016, that is a positive influence and significant quality of service to student loyalty. While The results for student satisfaction variables then obtained t count value of 4.901 with a p-value of 0.000, that is a positive influence and significant student satisfaction on student loyalty. Keywords: Service Quality, Satisfaction and Student’s Loyalty.